A method for monitoring glacial loss and temperature variation using satellite observations: Case study of Pico de Orizaba and Iztaccíhuatl (Mexico). Issue 1 (1st January 2019) - Viola, Donna; McKay, Christopher P.; Navarro-González, Rafael
ABSTRACT: Throughout the world, tropical glaciers are rapidly receding and some are at risk of complete loss within the next several decades. It is therefore important to monitor these glacial regions to better understand the factors affecting glacier loss and risks to nearby communities. Here, we provide an update on the summit glacier extents of Pico de Orizaba (19.03°N, 97.27°W) and Iztaccíhuatl (19.18°N, 98.64°W) in central Mexico, reporting areas every 1–11 years between 2001 and 2019 (depending on the availability of high-quality imagery). Glacier extents are derived from multispectral satellite imagery (Landsat 7–8 and the European Space Agency's Sentinel-2) using a semi-automated mapping method that takes the ratio of the near-infrared (or panchromatic) and shortwave infrared bands and applies appropriate threshold(s) for glacier identification. We also use thermal band imagery from Landsat 7–8 to estimate surface temperatures of both the glaciers and the surrounding terrain to provide a more comprehensive understanding of the summit environment. We find that glacier retreat has continued on both summits, and surface temperatures (even over glacier ice) can be at or near the melting point of water during some parts of the year, particularly on lower-elevation Iztaccíhuatl, suggesting a risk of continued ice loss in the future.